Guidelines on newly identified limitations of diagnostic tools for COVID‐19 and consequences - Syal, Kirtimaan (Journal of medical virology, 2021)
Coronavirus disease 2019 (COVID‐19) caused by coronavirus has spread worldwide and has become the deadliest pandemic of the 21st century. Such rapid spread is predominantly attributed to the poor diagnosis and its asymptomatic transmission. In the absence of treatment regime, timely diagnosis is the best available remedy that can restrict its spread. An early diagnosis of COVID‐19 is critical for determining the line of treatment and preventing long term complications in the infected subject. Unfortunately, available rapid antigen and antibody kits are known to be erroneous whereas reverse transcription polymerase chain reaction based tests are expensive, viral load dependent and at times inconclusive. In current scenario, the false‐negative results imposed a major risk to the individual patient care and also to the efforts for containing the spread at the population level, where as false positives are traumatic for families and can lead to improper treatment resulting in severe complications. In this article, the limitations of available diagnostic procedures have been elaborated and plausible combination approach has been advised.